“PROYECTO DE FACTIBILIDAD PARA LA IMPLEMENTACIÓN DE UN CENTRO DE CAPACITACIÓN ARTESANAL EN BELLEZA, EN EL CANTÓN GONZANAMÁ” - Torres Riofrío, María Yulieth (2024)
The present research entitled "Feasibility project for the implementation of an artisan training center in beauty, in the canton Gonzanamá, province of Loja", its main objective was to determine the financial feasibility for the implementation of an artisan training center in beauty in the canton, for this, a descriptive-exploratory methodology was used, which allowed applying the technique of the survey to a sample of 348 women over 15 years, the same that were considered as target market, having an acceptance of 86.81% for the implementation of the training center in the sector. In addition, a market study was conducted which determined a totally unsatisfied demand in reference to the service of artisan training in beauty; a technical study, which determined that the location of the center is in the cantonal head for ease of access for students and for the supply of basic services, the center will have an infrastructure of 151m2 divided into administrative sections and classrooms necessary for learning-teaching, having a capacity for 180 students per year; a financial study, in which the initial investment was set at US$96,491.99 of which 50% was contributed by the partners and 50% by BanEcuador at an interest rate of 16.30%; the financial evaluation allowed demonstrating the feasibility of the project due to its NPV is positive with US$27,291.43 dollars, the IRR is positive with 27.18%, the RBC is 0.52 dollars of profit for each dollar unit invested, and the PRC is 3 years, 10 months, 20 days, also, to know the sensitivity of the project after increase in costs and decrease in income by 2.27% corresponding to the country risk and inflation rate, being its result of 0.30 and 0.47 respectively, therefore, it is considered that the project has low sensitivity.